Brand building development through social media platforms: Case study of Mrs. Santa Claus Finland Oy - Fanny, Fanny (2021)
Mrs. Santa Claus Finland Oy is a service company that has been established in 2015, however, the company still cannot meet the expected profit. During the Covid-19 pandemic, the service cannot be held face to face, instead, the services are conducted online. Hence a method needs to be formulated, to make the brand to be more recognizable as well as more profitable. Based on the background, the goal of this thesis is to define guidelines for brand-building development through social media platforms. Since The reason for this is that not all companies have optimized the use of social media so that their brands can be better known by the wider community. Eventually, the companies especially the case company in this study, are expected to have a better understanding of social media management. Desk research, benchmarking and interview are the research methods to seek the needed data and information in this study. At desk research method, all the information is taken from existing online articles using OAMK library and through Google Scholar as the search engines. Two companies involved in the same business as Mrs. Santa Claus Finland Oy were chosen as the research object in benchmarking. One company is in Rovaniemi, Finland and the other is located in Las Vegas, USA. An interview was conducted with Mrs. Rundgren (owner of Mrs. Santa Claus Finland Oy) as the interviewee to get a view on the current use of social media in the case company. The research results have defined three points. Firstly, brand building in social media is important in the current time because social media existence has impacted conducting business. Some elements such as entertainment; hashtag; influencer,story telling; rich media content and customer emotion can assist in brand building on social media platforms. Lastly, challenges that shall be faced when doing brand building on social media platforms The research finding figures out the use of social media in the world which covers several areas. The global digital population can give an idea of how big the digital population compared to the world population. The information on countries with the highest number of users helps to understand which country can be targeted for social media brand-building development. Then cover-age of most used social media platforms and social media popularity gives an idea on which social media has the most users. The given suggestions cover finding new formats brand building elements which can be applied easily by Mrs. Santa Claus Finland Oy. companies. The customer emotion, storytelling and hashtags elements should be included in the published content, lastly companies Mrs. Santa Claus Finland Oy better focus just on a limited number of social media platforms only.